Changes in Feed Proanthocyanidin Profiles during Silage Production and Digestion by Lamb - Girard Marion; Lehtimäki Annika; Bee Giuseppe; Dohme-Meier Frigga; Karonen Maarit; Salminen Juha-Pekka (MDPI, 2022)
Proanthocyanidins are plant specialized metabolites which are beneficial to animal nutrition and health. This study determined how proanthocyanidin profiles of sainfoin (Onobrychis viciifolia) and birdsfoot trefoil (Lotus corniculatus) change during the forage conservation process and along the digestive tract of lamb. We determined soluble, protein- and fiber-bound proanthocyanidins by spectrophotometric methods and soluble proanthocyanidin profiles by UPLC-MS/MS. During the conservation process, the total proanthocyanidin contents reduced in both forages and the relative proportion of insoluble proanthocyanidins increased, especially in sainfoin. The soluble proanthocyanidins, their mean degree of polymerization and the relative prodelphinidin share declined in both feed species. In the abomasum of lambs fed sainfoin silage, most of the proanthocyanidins were in insoluble form bound to proteins and fibers, but in the small and large intestines, the proportion of soluble proanthocyanidins increased again. For lambs fed birdsfoot trefoil, the trend was not so clear as proanthocyanidins were already mainly soluble in the abomasum. Nevertheless, a large part of soluble proanthocyanidins was recovered in the digestive tract but could not be detected by the UPLC-MS/MS method used. This study suggests that proanthocyanidins have probably been metabolized in the digestive tract by the resident microbiota.